Penyuluhan Dan Pelatihan Masyarakat Ibu Dan Anak RT 004, Kel Pulogadung, Kec Pulogadung, Jakarta Timur Mengenai Kesehatan Gigi Dan Mulut Serta Penggunaan Obat Kumur - Halim, Himawan; Natassya, Priska; Ariesanti, Yessi; Yuliarsi, Yayuk; Farizka, Intan (JURNAL ABDIMAS KESEHATAN TERPADU, 2024)
The COVID-19 pandemic is a valuable lesson and experience for the world community in facing challenges to maintain health and daily life. The psychological and emotional impact of the COVID-19 pandemic on family behavior and society in general. Dental and oral health education for children other than mothers is one of the health efforts that can be carried out to increase the knowledge, willingness and skills of children and mothers as a large family in maintaining dental and oral health and hygiene. Explanations need to be given to children and mothers about why and how to maintain healthy teeth and mouth properly. Dental and oral health education delivered in the form of stories through audiovisual media and simulations will be able to create a pleasant learning atmosphere so that it is more effective in attracting attention and facilitating the process of absorbing information by parents, especially children.